Analisis Teori Produksi dan Distribusi Islam - Sri Rahma; Nasya Mykayla; Ajeng Puspita Dewi; Sabila Agustina Putri S.; Suhailah Meilani (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Production theory becomes the most important part to be studied in meeting individual needs for goods. However existing production has not been able to meet the needs of each individual, so uneven production causes many regions to lack food and other needs. his research is a literature research with descriptive qualitative analysis. Data sources are obtained through searching internet sources in the form of Qur'an and Hadith sources, books, national and international articles, and online news. The analysis technique used is content analysiswhich focuses on the perspective of Islamic economics. This study concludes that the theory of production in conventional economics is based on the Homo Economicus paradigm independent of moral guidance. However, Production Theory from an Islamic perspective is based on the Homo Islamicus Paradigm which implements the objectives of sharia (maqashid sharia). In Islamic economics, research on distribution has always been a heated debate because it talks not only about economic aspects but also about social and political aspects. Therefore, to this day, this research has attracted the attention of Islamic and conventional economic thinkers. The purpose of this research is to interpret and provide an explanation of data related to current circumstances, public perspectives and attitudes, conflicts between two or more situations, influences on certain conditions, and other factors. To lay the theoretical foundations for this qualitative descriptive research, researchers used library studies to gather information from books, magazines, newspapers, and other literature